Ageratum enation virus Infection Induces Programmed Cell Death and Alters Metabolite Biosynthesis in Papaver somniferum - Srivastava, Ashish; Agrawal, Lalit; Raj, Rashmi; Jaidi, Meraj; Raj, Shri K.; Gupta, Swati; Dixit, Ritu; Singh, Poonam C.; Tripathi, Tusha; Sidhu, Om P.; Singh, Brahma N.; Shukla, Sudhir; et al. (Frontiers in Plant Science, 2017)
A previously unknown disease which causes severe vein thickening and inward leaf curl was observed in a number of opium poppy (Papaver somniferum L.) plants. The sequence analysis of full-length viral genome and associated betasatellite reveals the occurrence of Ageratum enation virus (AEV) and Ageratum leaf curl betasatellite (ALCB) respectively. Co-infiltration of cloned agroinfectious DNAs of AEV and ALCB induces the leaf curl and vein thickening symptoms as were observed naturally. Infectivity assay confirmed this complex as the cause of disease and also satisfied the Koch’s postulates. Comprehensive microscopic analysis of infiltrated plants reveals severe structural anomalies in leaf and stem tissues represented by unorganized cell architecture and vascular bundles. Moreover, the characteristic blebs and membranous vesicles formed due to the virus-induced disintegration of the plasma membrane and intracellular organelles were also present. An accelerated nuclear DNA fragmentation was observed by Comet assay and confirmed by TUNEL and Hoechst dye staining assays suggesting virus-induced programmed cell death. Virus-infection altered the biosynthesis of several important metabolites. The biosynthesis potential of morphine, thebaine, codeine and papaverine alkaloids reduced significantly in infected plants except for noscapine whose biosynthesis was comparatively enhanced. The expression analysis of corresponding alkaloid pathway genes by real time-PCR corroborated well with the results of HPLC analysis for alkaloid perturbations. The changes in the metabolite and alkaloid contents affect the commercial value of the poppy plants.